Multidrug Resistant Uropathogenic Escherichia coli ST405 With a Novel, Composite IS26 Transposon in a Unique Chromosomal Location - Roy Chowdhury, Piklu; McKinnon, Jessica; Liu, Michael; Djordjevic, Steven P. (Frontiers in Microbiology, 2019)
Escherichia coli ST405 is an emerging urosepsis pathogen, noted for carriage of blaCTX-M, blaNDM, and a repertoire of virulence genes comparable with O25b:H4-ST131. Extraintestinal and multidrug resistant E. coli ST405 are poorly studied in Australia. Here we determined the genome sequence of a uropathogenic, multiple drug resistant E. coli ST405 (strain 2009-27) from the mid-stream urine of a hospital patient in Sydney, Australia, using a combination of Illumina and SMRT sequencing. The genome of strain 2009-27 assembled into two unitigs; a chromosome comprising 5,287,472 bp and an IncB/O plasmid, pSDJ2009-27, of 89,176 bp. In silico and phenotypic analyses showed that strain 2009-27 is a serotype O102:H6, phylogroup D ST405 resistant to ampicillin, azithromycin, kanamycin, streptomycin, trimethoprim and sulphafurazole. The genes encoding resistance to these antibiotics reside within a novel, mobile IS26-flanked transposon, identified here as Tn6242, in the chromosomal gene yjdA. Tn6242 comprises four modules that each carries resistance genes flanked by IS26, including a class 1 integron with dfrA17 and aadA5 gene cassettes, a variant of Tn6029, and mphA. We exploited unique genetic signatures located within Tn6242 to identify strains of ST405 from Danish patients that also carry the transposon in the same chromosomal location. The acquisition of Tn6242 into yjdA in ST405 is significant because it i) is vertically inheritable; ii) represents a reservoir of resistance genes that can transpose onto resident/circulating plasmids; and iii) is a site for the capture of further IS26-associated resistance gene cargo.